Long Term Effects of the COVID-19 Pandemic on Social Concerns - Blanco, Esther; Baier, Alexandra; Holzmeister, Felix; Jaber-Lopez, Tarek; Struwe, Natalie (Frontiers in Psychology, 2021)
While some local, temporary past crises have boosted overall charitable donations, there have been concerns about potential substitution effects that the Covid-19 pandemic might have on other social objectives, such as tackling climate change and reducing inequality. We present results from a donation experiment (n = 1,762), with data collected between April 2020 and January 2021. We combine data from (i) an online donation experiment, (ii) an extended questionnaire including perceptions, actions, and motives on the Covid-19 pandemic, the climate crisis, and poverty, as well as charitable behavior and (iii) epidemiological data. The experimental results show that donations to diverse social concerns are partially substituted by donations to the Covid-19 fund; yet, this substitution does not fully replace all other social concerns. Over time we observe no systematic trend in charitable donations. In regards to the determinants of individual donations, we observe that women donate more, people taking actions against Covid-19 and against poverty donate more, while those fearing risks from poverty donate less. In addition, we observe that the population under consideration is sensitive to the needs of others, enhancing total donations for higher Covid-19 incidence. For donations to each charity, we find that trusting a given charitable organization is the strongest explanatory factor of donations.